"Live high-train low" using normobaric hypoxia: a double-blinded, placebo-controlled study - Siebenmann, C.; Robach, P.; Jacobs, R. A.; Rasmussen, P.; Nordsborg, N.; Diaz, V.; Christ, A.; Olsen, N. V.; Maggiorini, M.; Lundby, C. (Journal of Applied Physiology, 2012)
The combination of living at altitude and training near sea level [live high-train low (LHTL)] may improve performance of endurance athletes. However, to date, no study can rule out a potential placebo effect as at least part of the explanation, especially for performance measures. With the use of a placebo-controlled, double-blinded design, we tested the hypothesis that LHTL-related improvements in endurance performance are mediated through physiological mechanisms and not through a placebo effect. Sixteen endurance cyclists trained for 8 wk at low altitude (<1,200 m). After a 2-wk lead-in period, athletes spent 16 h/day for the following 4 wk in rooms flushed with either normal air (placebo group, n = 6) or normobaric hypoxia, corresponding to an altitude of 3,000 m (LHTL group, n = 10). Physiological investigations were performed twice during the lead-in period, after 3 and 4 wk during the LHTL intervention, and again, 1 and 2 wk after the LHTL intervention. Questionnaires revealed that subjects were unaware of group classification. Weekly training effort was similar between groups. Hb mass, maximal oxygen uptake (VO(2)) in normoxia, and at a simulated altitude of 2,500 m and mean power output in a simulated, 26.15-km time trial remained unchanged in both groups throughout the study. Exercise economy (i.e., VO(2) measured at 200 W) did not change during the LHTL intervention and was never significantly different between groups. In conclusion, 4 wk of LHTL, using 16 h/day of normobaric hypoxia, did not improve endurance performance or any of the measured, associated physiological variables.